Direct flights and cross-border mergers & acquisitions - Zhang, Chi; Kandilov, Ivan T.; Walker, Mark D. (Journal of Corporate Finance, 2021)
Prior evidence indicates that proximity increases investments resulting in stronger economic growth. The introduction of a non-stop direct flight between two locations in different countries allows for faster travel and a lower cost of acquiring information, potentially facilitating acquisitions abroad. We examine this channel by considering cross-border mergers and acquisitions (M&A) activity between China and the U.S. Our results suggest that direct flights matter most in target selection. Direct flights are more important for M&A activity where information asymmetry is greater and for first time acquirers in the market. We demonstrate that endogeneity is unlikely to drive the results.